Editorial: self‐dilation for refractory oesophageal strictures is worth considering. Issue 2 (25th June 2018) - Heading, R. C.
Abstract : Linked Content This article is linked to Qin et al and Halland papers. To view these articles visithttps://doi.org/10.1111/apt.14807 andhttps://doi.org/10.1111/apt.14839 .